CCNP BCMSN Quick Reference Sheets. - Stewart, Brent (Cisco Press, 2006)
CCNP Quick Reference Sheets Bundle (Digital Short Cut) Brent Stewart, Denise Donohue, Jay Swan ISBN: 1-58705-327-6 As a final exam preparation tool, the four CCNP Quick Reference Sheets included in this value-priced bundle provide a concise review of all objectives on all four of the new CCNP exams (BSCI 642-901, BCMSN 642-812, ISCW 642-825, and ONT 642-845). These digital Short Cuts provide you with detailed, graphical-based information, highlighting only the key topics in cram-style format. With these documents as your guide, you will review key concepts required to manage the routers and switches that form the network core, as well as edge applications that integrate voice, wireless, and security into the network. These fact-filled Quick Reference Sheets allow you to get all-important information at a glance, helping you to focus your study on areas of weakness and to enhance memory retention of essential exam concepts. Table of Contents: 1. CCNP BSCI Quick Reference Sheets 2. CCNP BCMSN Quick Reference Sheets 3. CCNP ONT Quick Reference Sheets 4. CCNP ISCW Quick Reference Sheets Brent Stewart, CCNP, CCDP, MCSE, is a network administrator for CommScope and a certified Cisco Systems instructor. He participated in the development of BSCI and has seperately developed trainingmaterial for ICND, BSCI, BCMSN, BCRAN, and CIT. Brent lives in Hickory, NC, with his wife, Karen and children, Benjamin, Kaitlyn, Madelyn, and William. Denise Donohue, CCIE No. 9566, is manager of solutions engineering for ePlus Technology in Maryland. She is responsible for designing and implementing data and VoIP networks, supporting companies based in the National Capital region. Prior to this role, she was a systems engineer for the data consulting arm of SBC/AT & T. Denise was a Cisco instructor and course director for Global Knowledge and did network consulting for many years. Her CCIE is in Routing and Switching. Jay Swan is a senior network engineer for the Southern Ute Indian Tribe Growth Fund in Ignacio, CO. Prior to this position, he was a Cisco instructor and course director for Global Knowledge. Jay has also worked in IT in the higher education and service provider fields. He holds CCNP® and CCSP® certifications.